Proceedings of the SIGCHI Conference on Human Factors in Computing Systems - CHI '93 1993
DOI: 10.1145/169059.169179
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of earcons for use in auditory human-computer interfaces

Abstract: An evaluation of earcons was carried out to see whether they are an effective means of communicating information in sound. An initial experiment showed that earcons were better than unstructured bursts of sound and that musical timbres were more effective than simple tones. A second experiment was then carried out which improved upon some of the weaknesses shown up in Experiment 1 to give a significant improvement in recognition. From the results of these experiments some guidelines were drawn up for use in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
174
0
3

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(179 citation statements)
references
References 8 publications
2
174
0
3
Order By: Relevance
“…Simple Earcons [19,20] were used for the audio feedback. Earcons are abstract, synthetic tones that can be used in structured combinations to create sound messages to represent parts of an interface.…”
Section: Sounds Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…Simple Earcons [19,20] were used for the audio feedback. Earcons are abstract, synthetic tones that can be used in structured combinations to create sound messages to represent parts of an interface.…”
Section: Sounds Usedmentioning
confidence: 99%
“…By using more complex manipulations of the parameters of sound hierarchical earcons can be created [21] which allow the representation of hierarchical structures. Detailed investigations of earcons by Brewster, Wright & Edwards [19] showed that they are an effective means of communicating information in sound. The sounds were designed using earcon construction guidelines proposed by Brewster et al [22], given the restrictions imposed by the Palm III.…”
Section: Sounds Usedmentioning
confidence: 99%
“…Introduced by Brewster et al [3], they are described as structured abstract messages that can be used to communicate messages via vibration patterns. Guidelines for their design are presented in [15]. As an example, tactons can be formed by varying frequencies f a and f b in (1).…”
Section: Related Workmentioning
confidence: 99%
“…The set of four tactons that could be associated to each risk is already sets by preliminary experimentation. Here, used tactons are designed according to the guidelines presented in [15].…”
Section: Rewards Zonementioning
confidence: 99%
“…Prosody manipulation, however, was very successful on providing the means for header/data cell distinction and row start/end within a nested structure [3]. Earcons and auditory icons have been used extensively in auditory humancomputer interfaces [19]. Earcons are used to communicate context such as hierarchies [20], depict visual categorisation [21], for menu navigation in graphical user interfaces [22], telephone interfaces [23] and mobile phones [24].…”
Section: Problem Formulationmentioning
confidence: 99%